Belgo‐Congolese Transnational Comics Esthetics: Transcolonial Labor from Mongo Sisse's Bingo en Belgique to Cassiau‐Haurie and Baruti's Madame Livingstone: Congo, la Grande Guerre (2014). Issue 5 (May 2016) - Bragard, Véronique
Abstract: This article investigates the development of genealogies of Belgo–Congolese comics showing how the migrations of Congolese artists have catalyzed a re‐fashioning of the genre's form and themes, leading to new engaged postcolonial aesthetics that connect with a long and brutal history of labor. Starting from Mongo Sisé's Bingo en Belgique and Baruti's publication of Mme Livingstone (2014), it looks at the Belgo–Congolese transnational aesthetic voice that has been developing between Belgium and the Congo and in the tensions/irony/hybridity of the images. Both authors highlight the creation of cultural forms "from below" and across boundaries, purposely as carried and shaped by artistic migration histories – of the Congolese Force Publique, of soldiers who migrated (sometimes forcefully for WWI, for instance) across the continent and artists – within international, colonial, and neocolonial–geopolitical economies.